PECULIARITIES OF DEVELOPMENT OF PEDAGOGICAL COMPETENCE OF STUDENTS - Ibragimova Shoira Kosimovna (American Journals, 2023)
This article presents the concept of competence and information about competence, specific features of the development of pedagogical competence of students.
Keywords: competence, competence, professional, special, pedagogical, intellectual, system